Children’s Treatment Experiences in Pediatric Cancer Care Using Semi-Immersive Virtual Reality: Integrating Children’s Experiences and Parental Narratives - Margaretha, Sumarti Endah Purnamaningsih Maria; Purwaningsih, Iswanti; Widiastuti, Zeni (Chakra Brahmanda Lentera Institute, 2026)
Background: Childhood cancer remains a major global health challenge, with leukemia being the most common malignancy among children. Chemotherapy often causes substantial physical and psychological distress that negatively affects children's treatment experiences. Although previous studies have reported that Semi-Immersive Virtual Reality (SIVR) may reduce pain, anxiety, and procedural distress, little qualitative evidence has explored children's treatment experiences by integrating children's own perspectives with parents' narratives. Therefore, this study explored children's treatment experiences during chemotherapy using SIVR across different developmental stages. Methods: A qualitative descriptive study following the Consolidated Criteria for Reporting Qualitative Research (COREQ) guideline employed purposive sampling. Seventy children undergoing chemotherapy participated in the SIVR intervention. Children aged >6 years participated in individual semi-structured interviews, whereas parents of children aged ≤6 years participated in semi-structured Focus Group Discussions (FGDs) as proxy informants. Interviews and FGDs were audio-recorded, transcribed verbatim, and analyzed using Braun and Clarke's thematic analysis. Trustworthiness was established through member checking, data triangulation, and audit trails. Results: Five interconnected themes with several categories described children's emotional, physical, and behavioral treatment experiences: (1) treatment burden and emotional strain, (2) SIVR as emotional escape and comfort, (3) physical and ergonomic limitations, (4) treatment engagement and coping, and (5) acceptability and future expectations. Integrating children's interviews with parents' narratives provided complementary insights across developmental stages, with participants describing greater emotional comfort and coping despite ergonomic challenges. Conclusion: The findings suggest that SIVR may serve as a promising supportive intervention for enhancing children's treatment experiences during chemotherapy. Integrating children's interviews with parents' narratives provides comprehensive evidence to support child-centered pediatric oncology care. Future multicenter qualitative or mixed-methods studies should evaluate ergonomically optimized SIVR to strengthen evidence for broader clinical implementation.